2023
DOI: 10.2215/cjn.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PLA2R Antibody Levels and Clinical Risk Factors for Treatment Nonresponse in Membranous Nephropathy

Abstract: Background: The 2021 KDIGO guidelines recommend following anti-PLA2R antibody levels as a marker of treatment response in membranous nephropathy, however the optimal timing to evaluate antibody levels and how to combine them with other clinical variables are currently unknown. Methods: We used a cohort of 85 patients from the MENTOR trial with anti-PLA2R antibodies ≥14 RU/ml to identify risk factors for not experiencing proteinuria remission after 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Cases with immunologic remission not followed by remission of NS have been described [ 69 ] and recent evidence suggests that baseline anti-PLA2R titres do not predict disease progression with such confidence after adjusting for proteinuria and kidney function [ 75 , 76 ]. A subanalysis of the MENTOR trial (NCT01180036) showed that anti-PLA2R antibody titres combined with serum albumin levels after 3 months of treatment was the best method to evaluate the probability of remission [ 77 ]. Serum albumin levels are of great value considering that proteinuria can show fluctuations caused by haemodynamic changes or inaccurate urine collection.…”
Section: Tip 7 Monitor and Personalize Ist By Closely Measuring Kidne...mentioning
confidence: 99%
“…Cases with immunologic remission not followed by remission of NS have been described [ 69 ] and recent evidence suggests that baseline anti-PLA2R titres do not predict disease progression with such confidence after adjusting for proteinuria and kidney function [ 75 , 76 ]. A subanalysis of the MENTOR trial (NCT01180036) showed that anti-PLA2R antibody titres combined with serum albumin levels after 3 months of treatment was the best method to evaluate the probability of remission [ 77 ]. Serum albumin levels are of great value considering that proteinuria can show fluctuations caused by haemodynamic changes or inaccurate urine collection.…”
Section: Tip 7 Monitor and Personalize Ist By Closely Measuring Kidne...mentioning
confidence: 99%
“… 164 Furthermore, studies have showcased its capacity to reverse epitope spread. 165 , 166 After undergoing RTX treatment, a significant majority of individuals with IMN experience either complete or partial remission (CR or PR), 167 with an impressive overall remission rate of 83.12%. 168 Remarkably, it has demonstrated superiority over cyclosporine in sustaining the remission of proteinuria.…”
Section: Treatment Strategies For Mnmentioning
confidence: 99%